DEVELOPING AN ENVIRONMENTALLY SAFE AND RESOURCE-SAVING BIOTECHNOLOGY FOR COTTON CULTIVATION IN THE SALINE SOILS OF BUKHARA REGION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes resource-saving and environmentally safe biotechnological approaches to cotton cultivation on saline soils of the Bukhara region. It examines the factors affecting cotton growth under salinity conditions, biotic and abiotic methods of soil improvement, as well as new technologies developed based on biofertilizers, microorganisms, and green microalgae. The results of the research identify opportunities to increase cotton yield, reduce water and mineral fertilizer consumption, and ensure environmental sustainability.